2018
DOI: 10.3390/ma11091597
|View full text |Cite
|
Sign up to set email alerts
|

Force Prediction for Incremental Forming of Polymer Sheets

Abstract: Incremental sheet forming (ISF) is gaining attention as a low cost prototyping and small batch production solution to obtain 3D components. In ISF, the forming force is key to define an adequate setup, avoiding damage and reducing wear, as well as to determine the energy consumption and the final shape of the part. Although there are several analytical, experimental and numerical approaches to estimate the axial forming force for metal sheets, further efforts must be done to extend the study to polymers. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Marques et al [ 13 ] found that an increase in stress triaxiality promotes damage and fracture in the polymers. Medina-Sanchez et al [ 14 ] proposed a model to predict the forming force. Martins et al [ 15 ] identified wrinkling and fracture as two failure modes in the ISF of thermoplastics.…”
Section: Introductionmentioning
confidence: 99%
“…Marques et al [ 13 ] found that an increase in stress triaxiality promotes damage and fracture in the polymers. Medina-Sanchez et al [ 14 ] proposed a model to predict the forming force. Martins et al [ 15 ] identified wrinkling and fracture as two failure modes in the ISF of thermoplastics.…”
Section: Introductionmentioning
confidence: 99%
“…The forces during the SPIF of different polymeric materials were analysed by Medina-Sanchez et al [7]. This study was a combined analytical-numerical-experimental study for polycarbonate sheets and polyvinylchloride sheets.…”
Section: State Of the Artmentioning
confidence: 99%
“…As demonstrated, the maximum forming force is decreased with the increased spindle speed and the decreased tool radius. To predict axial force in SPIF of thermoplastic sheets, two procedures were proposed by Medina-Sanchez et al [73], the first of which is based on the finite element simulation, the other is a simple semi-analytical model. The results showed reasonable agreement with the experimental measurements with a relative error of less than 10%.…”
Section: Forming Forcementioning
confidence: 99%